2017
DOI: 10.1136/bcr-2016-218807
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal pregnancy? Evaluation of elevated hCG in a 59-year-old woman

Abstract: Slightly elevated serum human chorionic gonadotropin (hCG) can be a normal finding in postmenopausal women. We report a case of a 59-year-old woman with a history of abnormal uterine bleeding who presented with a concern for pregnancy after developing nausea and vomiting a few weeks after unprotected intercourse. Although pregnancy was extremely unlikely, hCG was obtained in order to reassure the patient since she reported that her mother conceived at the age of 60. Serum hCG was positive, prompting concern fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Values of beta-hCG in the indeterminate (5-25 IU/L) or positive range (>25 IU/L) prompt additional workup to rule out pregnancy or malignancies [6]. Additionally, elevated serum beta-hCG has also been a reported finding in postmenopausal females, with 6%-8% having an increased value; however; it is not a well-known trend (Table 1) [7]. Early normal pregnancy >50…”
Section: Discussionmentioning
confidence: 99%
“…Values of beta-hCG in the indeterminate (5-25 IU/L) or positive range (>25 IU/L) prompt additional workup to rule out pregnancy or malignancies [6]. Additionally, elevated serum beta-hCG has also been a reported finding in postmenopausal females, with 6%-8% having an increased value; however; it is not a well-known trend (Table 1) [7]. Early normal pregnancy >50…”
Section: Discussionmentioning
confidence: 99%
“…Based on our knowledge and investigations, it seems that this case is the 745 th case of postmenopausal pregnancy reported in 1997–2018. [ 3 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In a study, vaginal bleeding was only associated with elevated Human Chorionic Gonadotropin (HCG) hormone. [ 3 ] In another study leech infestation was reported as the cause of vaginal bleeding, and reviewing studies since 1990 revealed only 2 cases of postmenopausal vaginal bleeding due to leech infestation. [ 2 3 ] In the current case, 7 years after the onset of menopause, “the patient's history of AUB led to a request for an abdominal ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this elevation of βhCG in nonpregnant women, especially in women around menopause, often leads the clinicians as well as those women to confusion. Detectable hCG in nonpregnant, perimenopausal women should raise concern because it is present in conditions which are often very rare: gestational trophoblastic diseases, ovarian germ cell tumors, paraneoplastic syndrome of some neoplasms and pituitary secretion of hCG 2 . Last, a false‐positive pregnancy test due to heterophile antibodies should also be considered 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Detectable hCG in nonpregnant, perimenopausal women should raise concern because it is present in conditions which are often very rare: gestational trophoblastic diseases, ovarian germ cell tumors, paraneoplastic syndrome of some neoplasms and pituitary secretion of hCG 2 . Last, a false‐positive pregnancy test due to heterophile antibodies should also be considered 1,2 . Here, we present the case of a 45‐year‐old amenorrheic woman with persistent elevation of serum βhCG levels, even after various interventions and cytostatic therapy.…”
Section: Introductionmentioning
confidence: 99%